AN EXPLORATORY STUDY ON SAMBALPURI DANCE AND MUSIC - Nath, Nibedita; Mishra, Supreeti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Dance and music are integral part of the cultural heritage of any community. The objective of the paper is to explore the different types of music and musical instruments used in Sambalpuri folk dance; to describe the different types of Sambalpuri folk dance and to throw light on the changes that are taking place in Sambalpuri music and dance due to several factors. The present study is exploratory and descriptive in nature.Data for the study was collected from both primary sources and secondary sources. Primary data were collected from the musicians, dancers, and dance teachers of Sambalpur district. Samples for the study were selected through the snowball sampling method. The findings of the study have been discussed under three sections. The first section describes the musical instruments associated with Sambalpuri folk dance. The second section deals with the different types of Sambalpuri folk dance. The third section deals with changes that are taking place in Sambalpuri music and dance in courser of time due to several factors.